Functional Outcome of Closed Static Intramedullary Nailing with Distal two Plane Locking Versus Percutaneous Mippo Distal Tibial Locking Plate in Distal 3rd Tibia Metaphyseal Fractures - Muhammad Imran Haider, Kashif Siddiq, Ahmad Jamal, Muhamad Adeel Razzaque, Adnan Nazir, Muhammad Imran Anjum (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Aim of current study was to determine the functional outcomes of closed static intramedullary nailing with distal two plane locking versus percutaneous MIPPO distal tibial locking plate in distal 3rd tibia metaphyseal fractures. Study Design: Randomized clinical trial Place and Duration: Nishtar Hospital Multan/Qaisrani Medical Center Multan. Jan 2021-March 2022 Methods: There were 76 patients of both genders with age 15-60 years presented. All the patients had 3rd tibia metaphyseal fracture were admitted to hospital for surgery. Following the collection of informed written consent from enrolled patients, complete demographic information was gathered. Patients were equally divided into two groups. Group I received intramedullary nailing with distal two plane locking and group II received percutaneous MIPPO distal locking plate. Favorable and unfavorable outcomes among enrolled cases were compared. SPSS 22.0 was used to analyze all data. Results: There were majority males 22 (60.5%) in group I and 20 (52.6%) in group II. In group I mean age was 30.8±6.42 years with mean BMI 24.71±3.19 kg/m2 and in group II mean age was 31.14±3.58 years and had mean BMI 25.7±7.17 kg/m2. Falling, accidents, sports and lifting of heavy object was the most common cause of fractures. We found that intramedullary nailing was more effective as compared to MIPPO distal locking plate in terms of functional outcomes but difference was insignificant. Frequency of complications were higher in group II found in 14 (36.8%) as compared to group I in 4 (10.4%) cases. Conclusion: We concluded in this study that distal third tibial metaphyseal fractures were effectively operated by intramedullary nailing distal two plane locking and MIPPO distal locking plate but frequency of complications were higher in MIPPO group as compared to intramedullary nailing. Keywords: Metaphyseal Fractures, MIPPO Distal Platting, Intramedullary Nailling, Functional Outcomes, Complications